Canadian perspectives on loneliness; digital communication as meaningful connection - Dwyer, Lauren (Frontiers in Public Health, 2024)
This perspective piece considers loneliness and its relationship to communication, connection, and technology by reviewing the origins and lessons from the field. It begins with a search for an operational definition, then examines the differences between experiential (situational/isolationbased) and existential (continuous, non-situational) loneliness. Technology is addressed as both a hindrance and a tool for alleviating loneliness with the example of companion robots as an emerging technology for loneliness mitigation. Cultural differences in experiences of loneliness, specifically as a public health issue, are in the context of the COVID-19 pandemic in Canada. Concepts of social and emotional loneliness, individualism and collectivism, socioeconomic status, vulnerability, and lived experience are explored and provide an emphasis on 'meaningful connection' in the study of loneliness.